The Nordic Podcast 008 - Per Pippin Aspaas - Aspaas, Per Pippin; Veress, Dávid (The Nordic Podcast, 2020)
Source at https://www.stitcher.com/podcast/the-nordic-podcast Interview with Per Pippin Aspaas, Norwegian historian of sciences, vocal advocate of Open Access, and senior academic librarian in Tromsø.